Analyzing the Holes in the Art of Appraising. Issue 1 (March 2015) - Heineman, Anna
When a client hires an appraiser, he or she often assumes that the appraiser will give the correct value to the object. Yet, in the field of art appraising, when an appraiser misattributes a work of art or places an inappropriate value on an object either through malfeasance or negligence, it is the client whose pocketbook is at stake. The appraiser can be legally found at fault, but the onus is on the client to sue if the appraised value is too high or too low. This article aims to analyze the holes in the art appraisal system that can negatively affect the value placed on objects and offers recommendations of what to look for when commissioning an appraiser.